2019
DOI: 10.1111/dmcn.14144
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive functioning in children with neurofibromatosis type 1: relationship to cognition, behavior, and magnetic resonance imaging

Abstract: Aim To characterize the adaptive behavior profile of children with neurofibromatosis type 1 (NF1) and determine its relationship to neuropsychological functioning and non‐neoplastic T2‐weighted hyperintense brain lesions on brain magnetic resonance imaging (MRI). Method In this cross‐sectional study, we retrospectively reviewed neuropsychological reports from 104 children with NF1 (56 males, 48 females; mean age 10y 4mo; standard deviation [SD] 3y 4mo; range 3y 5mo–17y 6mo), and extracted data from a range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
6
15
1
1
Order By: Relevance
“…Another interesting result concerns the role of cognitive abilities in predicting behavioral problems: the presence of decreased intellectual abilities is associated to high level of externalizing behaviors; moreover, IQ revealed a significant factor influencing the extent of externalizing problems in addition to the presence of brain tumors. These data confirms that cognitive skills can be a facilitator of functional adaptation to the context and behavioral functioning in children with NF1 [44,45,46].…”
Section: Discussionsupporting
confidence: 74%
“…Another interesting result concerns the role of cognitive abilities in predicting behavioral problems: the presence of decreased intellectual abilities is associated to high level of externalizing behaviors; moreover, IQ revealed a significant factor influencing the extent of externalizing problems in addition to the presence of brain tumors. These data confirms that cognitive skills can be a facilitator of functional adaptation to the context and behavioral functioning in children with NF1 [44,45,46].…”
Section: Discussionsupporting
confidence: 74%
“…These aspects do not show a clear correlation with the disease severity according to the modified version of Riccardi medical severity scale. Of note however, this scale does not include cognitive and behavioral characteristics more directly involved in general adaptive functioning in daily-life [38].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have noted adaptive deficits in children with NF1 [15,62]. In a cross sectional study of 104 children with NF1, Eby et al [15] found that 46.5 percent of their sample demonstrated adaptive functioning impairment. They found mild reductions across Conceptual, Social and Practical skill domains.…”
Section: Adaptive Skillsmentioning
confidence: 98%
“…Research has also indicated that thalamic T2H as well as volume abnormalities in the corpus callosum, putamen, and amygdala are specifically associated with cognitive deficits in NF1 [11,14]. Of note, studies looking into the number of T2 spots and how this relates to cognitive impairment have been inconsistently documented [15].…”
Section: Neurofibromatosis Type 1 (Nf1)mentioning
confidence: 99%
See 1 more Smart Citation